Exploring Factors Behind Women Do Not Give Birth at Health Facilities in Nias Barat - Zebua, Sawato; Girsang, Ermi; Nasution, Sri Lestari Ramadhani; Ginting, Chrismis Novalinda (Universitas Aisyah Pringsewu, 2021)
Choosing a location for delivery by pregnant women and deliveries assisted by skilled health workers are important keys in reducing MMR and IMR. The low birth rate at health facilities in Mandrehe Utara Subdistrict, Nias Barat Regency is a serious challenge to achieve the success of the maternal and child health service program. This study analyzes the factors that influence pregnant women who do not give birth in health facilities. This study uses a quantitative method with a cross-sectional approach. The samples were 180 people. The data were collected using a questionnaire and then tested using the Chi-Square test and logistic regression test. The results showed that the reason why mothers did not choose to give birth in health facilities was influenced by knowledge (p=0.022), attitude toward birth attendants (p=0.002), perception of distance (p=0.004), husband and family support (p=0.000), and access to health information (p=0.007). The role of health workers had no significant effect in this study (p=0.756). The results of the logistic regression test showed that husband and family support was the most dominant variable affecting mothers who did not give birth in health facilities. Mothers who perceive the lack of support from their husbands and families are 5,668 times more to choose to give birth outside a health facility. Education and socialization by health workers to mothers and their husbands and families are suggested to increase knowledge, awareness and change attitudes. No less important are the government's efforts to provide health facilities and infrastructure development to reduce access difficulties.Pemilihan lokasi persalinan oleh ibu hamil dan persalinan yang ditolong tenaga kesehatan terampil menjadi kunci penting dalam menurunkan AKI dan AKB. Rendahnya angka persalinan di fasiltas kesehatan di Kecamatan Mandrehe Utara Kabupaten Nias Barat menjadi tantangan berat untuk mencapai keberhasilan program pelayanan kesehatan ibu dan anak. Studi ini bertujuan menganalisis faktor-faktor yang mempengaruhi ibu hamil tidak bersalin di fasilitas kesehatan. Studi ini menggunakan metode kuantitatif dengan pendekatan cross-sectional. Sampel yang terlibat sebanyak 180 orang. Pengumpulan data menggunakan kuesioner dan kemudian diuji dengan menggunakan uji Chi-Square dan uji regresi logistik. Hasil penelitian menujukkan penyebab ibu tidak memilih bersalin di fasilitas kesehatan dipengaruhi oleh pengetahuan (p=0,022), sikap terhadap penolong persalinan (p=0,002), persepsi tentang jarak (p=0,004), dukungan suami dan keluarga (p=0,000), dan akses terhadap informasi kesehatan (p=0,007). Peran petugas kesehatan tidak berpengaruh signifikan dalam studi ini (p=0,756). Hasil uji regresi logistik menunjukkan dukungan suami dan keluarga merupakan variabel yang paling dominan mempengaruhi ibu tidak melahirkan di fasilitas kesehatan. Ibu yang menganggap kurangnya dukungan suami dan keluarga berpeluang 5,668 kali memilih melahirkan di luar fasilitas kesehatan. Edukasi dan sosialisasi oleh tenaga kesehatan terhadap ibu beserta suami dan keluarga disarankan untuk peningkatan pengetahuan, kesadaran dan perubahan sikap. Tidak kalah penting upaya dari pemerintah untuk penyediaan fasilitas kesehatan dan pembangunan infrastruktur guna memangkas kesulitas akses.